Adding Insult to Injury: The Effects of Intimate Partner Violence Spillover on the Victim’s Reputation - Pagliaro, Stefano (Violence against women, 2022)
This article examined indirect consequences for the victims of intimate partner violence (IPV) in terms of ostracism and reputational threats. Through an experimental vignette survey, we compared bystanders’ reactions to either an intimate partner violence episode or a generic violence episode. A victim of IPV (vs. generic violence) received a more negative moral evaluation and was considered as more responsible for the violence perpetrated on her. This made participants not only anticipate a less positive reputation attributed to the victim but also report less willingness to approach and defend the victim and include her in relevant ingroups 1 year after the episode.